Rectus Femoris Transfer Improves Stiff Knee Gait in Children With Spastic Cerebral Palsy - Thawrani, Dinesh (Springer-Verlag, 2011)
BACKGROUND: Stiff knee gait is common among children with ambulatory cerebral palsy (CP). When surgery is indicated, rectus femoris transfer as a primary treatment enhances knee range of motion, reduces time to peak knee flexion, increases peak knee flexion, and reduces toe drag. QUESTIONS/PURPOSES: We determined whether (1) distal rectus femoris transfer improved knee range of motion, time to peak knee flexion, peak knee flexion, and toe drag in children with CP diagnosed with stiff knee gait; and (2) patients in some subgroups (eg, those with relatively high knee range of motion compared with those with low knee range of motion before rectus femoris transfer) had greater improvement in these parameters. METHODS: We retrospectively reviewed gait data from 56 patients (99 limbs) preoperatively, short-term, and long-term. Subgroup analyses were performed to determine whether patients with high knee range of motion relative to those with low or moderate knee range of motion improved differentially after rectus femoris transfer. The minimum followup was 7 years (mean ± SD, 10 ± 2 years; range, 7–13 years). RESULTS: The mean peak knee flexion increased from baseline to short-term and to long-term followup. Patients with low peak knee flexion had the greatest improvement of peak knee flexion after rectus femoris transfer relative to the moderate and high peak knee flexion subgroups. Similarly, the greatest improvement after rectus femoris transfer for knee range of motion occurred in the low knee range of motion subgroup relative to moderate and high subgroups. Rectus femoris transfer improved mean time to peak knee flexion at short-term and long-term followup compared with baseline. Likewise, there was a decrease in toe drag at short- and long-term after rectus femoris transfer. CONCLUSION: Distal rectus femoris transfer selectively improved peak knee flexion, toe drag, and reduced time to peak knee flexion in ambulatory children with CP with stiff knee gait. LEVEL OF EVIDENCE: Level IV, therapeutic study. See guidelines for authors for a complete description of levels of evidence.